TERAPI TA’LIMAH DAN MUHASABAH DALAM MENINGKATKAN SELF ESTEEM PADA PENYINTAS DEPRESI - Mohamat Hadori; Feby Amalia Syafitri (Fakultas Dakwah Universitas Ibrahimy, 2022)
Psychological factors are one of the supporting factors for the sustainability of human existence on this earth. Psychological factors include self-esteem. Low self-esteem can inhibit individual psychological growth. The findings in the field indicate that low self-estecan-em occur due to inappropriate parenting patterns. Z, the fourth of five children who are all boys. The different treatment that Z gets from his parents causes Z to have low self-esteem. Z’s low self-esteem causes Z to experience anxiety, sees himself as worthless, considers himself different from his siblings. Z also experienced symptoms of depression such as withdrawing from his social environment and seeing himself as just a burden which caused Z to have repeated thoughts about suicide, even Z had even attempted suicide. The purpose of this study is to increase Z’s self-esteem through ta’limah and muhasabah therapy. In ta’limah therapy, clients are given material and also given motivation. As a continuation of this ta’limah therapy, muhasabah therapy is also given. In muhasabah therapy, clients are given homework assignments in order for clients to use their minds positively so that clients can find meaning in their lives. Everything that happens to him is not in vain and he is someone of value. This study uses the type of action research or action research using a critical action research model because this research emphasizes a high intention to act to solve problems. This study consisted of two cycles, each cycle having four meetings. The final result of this research can be said to be successful, indicated by the change in Z’s thoughts and behavior in relation to his social environment, especially to his parents. Z has started to have positive thoughts about himself, no longer locks himself in his room, begins to interact with his family often, even thoughts about suicide Z also do not appear at the time of the implementation of the second cycle